EVALUATION OF INVESTMENT ATTRACTION OF UKRAINE BASED ON INTERNATIONAL RATINGS - Rudenko , V.V. (The actual problems of regional economy development, 2018)
In the article the methods of international research organizations in determining the investment attractiveness of the state are reviewed. The investment attractiveness of Ukraine on the basis of international ratings is carried out and the factors characterizing the attractiveness of the state for investors are determined. As a result of the study, it was found that Ukraine, according to international research organizations, has unattractive conditions for investment and needs urgent and radical reforms. Scientific novelty is related to the definition of the advantages and disadvantages of using international ratings to assess the investment attractiveness of the state. The practical significance is to offer concrete proposals on the prospects of Ukraine in attracting domestic and foreign investment.